Embryo movement is required for limb tendon maturation - Rolfe, Rebecca A.; Bastürkmen, Ebru Talak; Sliney, Lauren; Hayden, Grace; Dunne, Nicholas; Buckley, Niamh; McCarthy, Helen; Szczesny, Spencer E.; Murphy, Paula (Frontiers in Cell and Developmental Biology, 2024)
Following early cell specification and tenocyte differentiation at the sites of future tendons, very little is known about how tendon maturation into robust load-bearing tissue is regulated. Between embryonic day (E)16 and E18 in the chick, there is a rapid change in mechanical properties which is dependent on normal embryo movement. However, the tissue, cellular and molecular changes that contribute to this transition are not well defined. Here we profiled aspects of late tendon development (collagen fibre alignment, cell organisation and Yap pathway activity), describing changes that coincide with tissue maturation. We compared effects of rigid (constant static loading) and flaccid (no loading) immobilisation to gain insight into developmental steps influenced by mechanical cues. We show that YAP signalling is active and responsive to movement in late tendon.Collagen fibre alignment increased over time and under static loading. Cells organise into end-to-end stacked columns with increased distance between adjacent columns, where collagen fibres are deposited; this organisation was lost following both types of immobilisation. We conclude that specific aspects of tendon maturation require controlled levels of dynamic muscle-generated stimulation. Such a developmental approach to understanding how tendons are constructed will inform future work to engineer improved tensile load-bearing tissues.